2020
DOI: 10.1016/j.scitotenv.2020.141419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic and control measures on air quality and aerosol light absorption in Southwestern China

Abstract: China has been performing nationwide social lockdown by releasing the Level 1 response to major public health emergencies (RMPHE) to struggle against the COVID-19 (SARS-CoV-2) outbreak since late January 2020. During the Level 1 RMPHE, social production and public transport were maintained at minimal levels, and residents stayed in and worked from home. The universal impact of anthropogenic activities on air pollution can be evaluated by comparing it with air quality under such extreme conditions. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 41 publications
3
52
0
2
Order By: Relevance
“…China: (Agarwal et al, 2020;Chauhan and Singh, 2020;Chen et al, 2020a;Chen et al, 2020c;Chen et al, 2020d;Fan et al, 2020;G Huang and Sun, 2020;Lian et al, 2020;Liu et al, 2020c;Miyazaki et al, 2020;Nichol et al, 2020;Pei et al, 2020;Shakoor et al, 2020;Shi and Brasseur, 2020;Silver et al, 2020;Wan et al, 2020;Wang et al, 2020a;Wang et al, 2020b;Wang et al, 2020f;Xu et al, 2020c;Zhang et al, 2020a;Yuan et al, 2021) Other: (Ghahremanloo et al, 2020;Han et al, 2020;Ju et al, 2020;Ma and Kang, 2020;Zhang et al, 2020b) South Asia India: (Bedi et al, 2020;Beig et al, 2020;Biswal et al, 2020;Chatterjee et al, 2020;Gautam et al, 2020;Harshita and Vivek, 2020;Jain and Sharma, 2020;Kant et al, 2020;Kumari and Toshniwal, 2020;Panda et al, 2020;Ranjan et al, 2020;Selvam et al, 2020;Sharma et al, 2020a;Siddiqui et al, 2020;Singh and Chauhan, 2020;…”
Section: East Asiaunclassified
“…China: (Agarwal et al, 2020;Chauhan and Singh, 2020;Chen et al, 2020a;Chen et al, 2020c;Chen et al, 2020d;Fan et al, 2020;G Huang and Sun, 2020;Lian et al, 2020;Liu et al, 2020c;Miyazaki et al, 2020;Nichol et al, 2020;Pei et al, 2020;Shakoor et al, 2020;Shi and Brasseur, 2020;Silver et al, 2020;Wan et al, 2020;Wang et al, 2020a;Wang et al, 2020b;Wang et al, 2020f;Xu et al, 2020c;Zhang et al, 2020a;Yuan et al, 2021) Other: (Ghahremanloo et al, 2020;Han et al, 2020;Ju et al, 2020;Ma and Kang, 2020;Zhang et al, 2020b) South Asia India: (Bedi et al, 2020;Beig et al, 2020;Biswal et al, 2020;Chatterjee et al, 2020;Gautam et al, 2020;Harshita and Vivek, 2020;Jain and Sharma, 2020;Kant et al, 2020;Kumari and Toshniwal, 2020;Panda et al, 2020;Ranjan et al, 2020;Selvam et al, 2020;Sharma et al, 2020a;Siddiqui et al, 2020;Singh and Chauhan, 2020;…”
Section: East Asiaunclassified
“…Beyond gaseous pollutants and AOD, there are some studies analyzing the changes in BC concentrations during the lockdown period [26,[38][39][40][41][42], which reported significant reductions (30-70%), but with large variability among regions. On the contrary, only a few works examined the changes in aerosol spectral absorption [43,44], while there is a lack of studies related to changes in spectral-scattering and single-scattering albedo (SSA).…”
Section: Introductionmentioning
confidence: 99%
“…The model assumes that b abs is the sum of optical absorption coefficients of biomass burning (b abs,bb ) and fossil fuel (b abs,ff ) fractions, as given in Equations (6) and (7). b abs (370 nm) = b abs (370 nm) ff + b abs (370 nm) bb (6) b abs (880 nm) = b abs (880 nm) ff + b abs (880 nm) bb (7) The b abs,ff and b abs,bb are computed for the wavelengths of 370 and 880 nm using Equations (8) and (9), respectively, by assuming that b abs,bb is negligible at 880 nm [68,76]. The absorption exponents for fossil fuel (α ff ) and for biomass (α bb ) were used as 1 and 2, respectively.…”
Section: Black Carbon Measurements and Data Treatmentmentioning
confidence: 99%
“…A few studies have been conducted to reveal the impacts of COVID-19 lockdown measures on ambient BC concentrations. Reported studies from the USA [66], Italy [67], China [68,69], and India [70] revealed that BC concentrations reduced within the range between 22% and 71% in response to lockdown measures to combat the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%